African commitments for agricultural development goals and milestones for Niger - Diallo, Souleymane Sadio; Fofana, Ismaël; Diallo, Mariam Amadou (International Food Policy Research Institute, 2020)
The main objective of this study is to assess the potential contribution of agricultural investment to the achievement of Niger's economic and social development objectives. By combining a computable general equilibrium model and a microeconomic model, it helps to determine to what extent the implementation of the National Agricultural Investment Programme (NAIP) would enable Niger to achieve the objectives and targets of the CAADP, the United Nations’ SDGs and the African Union Agenda 2063. The results indicate that the implementation of the NAIP would enable the country to maintain the share of public agricultural expenditure above the 10% target set by CAADP. All things being equal, this would improve the attractiveness of the agricultural sector and increase both domestic and foreign private investment in the sector. Increased public and private investment could lead to agricultural GDP growth at a rate above the CAADP target of 6%, and to the achievement of several sustainable development goals by 2030 as well as some of the targets of the African Union's Agenda 2063. In particular, Niger could halve poverty by 2030. Similarly, the country could achieve the objective of sustainable growth and the creation of decent employment. However, reducing inequality and eradicating extreme poverty will remain major challenges for the country.